Inoculation of cucumber, melon and zucchini varieties with Tomato leaf curl New Delhi virus and evaluation of infection using different detection methods. (9th March 2017) - Figàs, M.R.; Alfaro‐Fernández, A.; Font, M.I.; Borràs, D.; Casanova, C.; Hurtado, M.; Plazas, M.; Prohens, J.; Soler, S.
Abstract: The disease caused by Tomato leaf curl New Delhi virus (ToLCNDV), which is naturally transmitted by the whitefly Bemisia tabaci, causes important economic losses in cucurbit crops. The availability of simple and efficient inoculation protocols and detection methods is necessary for screening varieties and germplasm collections as well as for breeding populations. We evaluated the infectivity of ToLCNDV inocula prepared using three different buffers for mechanical sap inoculation in a susceptible variety of zucchini. We found that inoculum prepared with buffer III, which contains polyvinylpyrrolidone, is highly efficient for mechanical inoculation, with 100% of plants displaying severe symptoms 21 days post‐inoculation. Using this buffer, we mechanically inoculated 19 commercial varieties of cucurbit crops (six of cucumber, six of melon and seven of zucchini), evaluated the evolution of symptoms and diagnosed infection using nine different ToLCNDV detection methods (four based on serology, four based on molecular hybridization and one based on PCR detection). The results revealed that all varieties are susceptible, although cucumber varieties display less severe symptoms than those of melon or zucchini. All detection methods were highly efficient (more than 85% of plants testing positive) in melon and zucchini, but in cucumber, the percentage of positive plants detected with serology and molecular hybridization methods ranged from 20.4% with Squash leaf curl virus (SLCV) antiserum, to 78.5% with DNA extract hybridization. Overall, the best detection results were obtained with PCR, with 92.6%, 92.4% and 98.4% cucumber, melon and zucchini plants, respectively, testing positive. When considering the overall results in the three crops, the best serology and molecular hybridization methods were those using Watermelon chlorotic stunt virus (WmCSV) antiserum and DNA extract, respectively. The inoculation methodology developed and the information on detection methods are of great relevance for the selection and breeding of varieties of cucurbit crops that are tolerant or resistant to ToLCNDV.